Aplikasi Panas sebagai Alternatif untuk Mengawetkan Kayu Heat Treatment as an Alternative for Wood Preservation - Jasni Jasni; Pipin Permadi; Didik A. Sudika; Rusti Rushelia (Masyarakat Peneliti Kayu Indonesia, 2004)
Most of Indonesian wood species are classified as less durable, so preservation is needed. Wood preservation inIndonesiamainly depends on imported preservatives. The preservatives are not only toxic to wood destroying organism but also to humans and the environments. Therefore alternative to treat wood should be sought and developed in term of the preservatives used as well as the methods. One that can be proposed is treating wood at high temperature combine with environmentally friendly preservatives, as tried in this experiment.The wood species used in this experiment were rubber wood (Hevea brasilliensis) and pine (Pinus merkusii). Both woods were treated with borax at two concentrations (3% and 5%) by cold-soaking method for 24 hours. The treated woods were subsequently air dried. Then those woods were treated at three levels of high temperature (180ºC, 200ºC, and 220ºC) in an oven for one hour. Finally, the treated wood samples were laboratory-tested by assessing their resistance to dry wood termites (Cryptotermes synocephalus Light.) and powder-post beetles (Heterobostrychus aequalis Wat).The results revealed that increases of heating temperature and concentration of preservatives resulted in more durable woods. In this regard their resistance to dry wood termite and powder-post beetles was increased as shown by smaller weight loss. Treating wood at temperature of 180ºC combined with borax at concentration of 3% resulted in 100% termite mortality on rubber wood and pine.